Distributed relay scheduling for maximizing lifetime in clustered wireless sensor networks - Zhang, Pengfei (2013)
Clustering and relaying techniques are important approaches towards mitigating the problem of finite network lifetime in wireless sensor networks. To this end, given a clustered wireless sensor network (WSN) (with defined cluster heads and their associated clusters) and a given relay node placement, we present a distributed service allocation algorithm for the relay node for maximizing network lifetime. We evaluate the performance of our method through theoretical analysis as well as simulations, and demonstrate the superior performance of our proposed method compared to a greedy periodic approach.